2021
DOI: 10.1002/cmm4.1185
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation analysis and chaos control of discrete prey–predator model incorporating novel prey–refuge concept

Abstract: This article investigates a prey–predator model incorporating a novel refuge proportional to prey and inverse proportion to the predator. We find conditions for the local asymptotic stability of fixed points of the proposed prey–predator model. This article presents Neimark–Sacker bifurcation (NSB) and period‐doubling bifurcation (PDB) at particular parameter values for positive equilibrium points of the proposed refuge‐based prey–predator system. The system exhibits the chaotic dynamics at increasing values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Adding relatively small amounts of prey refuge to the system has no effect on the chaotic behavior of the system. But adding a significant amounts of prey refuge to the system transforms the chaotic behavior into an oscillatory behavior and ultimately into a stable fixed point which resonates with the results in Jana [21] and Santra et al [35] (see Figure 1). The dynamics of system (5) are also significantly influenced by the intrinsic growth rate of prey population.…”
Section: Discussionsupporting
confidence: 86%
“…Adding relatively small amounts of prey refuge to the system has no effect on the chaotic behavior of the system. But adding a significant amounts of prey refuge to the system transforms the chaotic behavior into an oscillatory behavior and ultimately into a stable fixed point which resonates with the results in Jana [21] and Santra et al [35] (see Figure 1). The dynamics of system (5) are also significantly influenced by the intrinsic growth rate of prey population.…”
Section: Discussionsupporting
confidence: 86%
“…Sensitivity and bifurcation analyses have been performed on several models including the Kumar,Basu,Ghosh,Santra,Mahapatra [11] analysis of COVID-19 epidemic model; Santra, Mahapatra and Phaijo [12] bifurcation analysis and chaos control of discrete pre-predator model; Kumar, Basu, Santra, Ghosh and Mahapatra [13] optimal control design; Basu, Kumar, Santra, Mahapatra and Elsadany [14] Covid-19 pandemic's second wave's preventive control strategy; Kumar, Mahapatra, Parshad and Santra [15] model for dengue re-infection; Kumar, Santra and Mahapatra [16] stability and sensitivity analyses of the parameters of a SARS-CoV-2 model; Kumar,Basu, Santra, Elsadany, Elsonbaty, Mahapatraand Al-khedhairi [17] stability and sensitivity analyses of an Omicron variant epidemic's model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations of the predator-prey relationship with Ivlev-type functional responses have been conducted. Te results suggested that Iviev-type relationships between the species have a number of models in ecological applications, including dynamics in host-parasite models [16], predator-prey models [17][18][19][20][21][22][23][24][25], animal coat patterns [26], and phytoplankton-zooplankton model [27].…”
Section: Introductionmentioning
confidence: 99%